ANALISIS PENGARUH METODE PROBLEM BASED LEARNING TERHADAP PEMBENTUKKAN SOFT SKILL MAHASISWA DIII JTK POLBAN STUDI KASUS : MATA KULIAH PROYEK - Ida Suhartini (Jurnal Digit, 2018)
Abstract Project course is one of the subjects that aim to instill the formation of softskill. Problem Based Learning method applied in this course is meant to be able to form soft skill of student so hopefully there are positive characters that formed. The need for this planting in order to prepare students to be ready to compete in the industrial world. In the implementation of the question "how can this method affect the softskill", what things need to be improved so that this PBL method can be applied properly. This research uses quantitative method with correlational regression analysis toward two variables that is, problem based learning method in project subject with soft skill formation of DIII student of JTK Polban who have followed project course.server. Keywords: Softskill, PBL, Quantitative, regression, project